Auditoria em programas de preservação auditiva - Guirado , Débora Simões (2014)
The Hearing Conservation Program (HCP) aims prevent or stabilize the work related hearing loss through a dynamic process with opportunities for continuous improvement, which developed through planned and coordinated activities distributed in stages between different areas involved in the organization. The audit of the HCP, must act as an integrating element in which are gathered and interpreted information from all other program activities. The objective of this study is to perform an audit of HCP aimed at measuring the activities under the program, as well as the situational analysis of the performance of the HCP front of Brazilian law. The method consists of an evaluative research, retrospective, quantitative, which evaluated the HCP - Hearing Conservation Program implemented in three units of a company's lumber business. The measurement of the overall performance of the audit protocol applied in the HCP submitted the following percentages of compliances: drive 1-89%, unit 2-82% and unit 3-79% where it was possible to verify that the larger the deployment time of the HCP higher quality and compliance. The use of this protocol for audit could represent a major breakthrough for the systematization of HCP -related actions in organizations, focusing on the current requirements of Brazilian legislation, intended to quantify and qualify adaptations flaws in the process, supporting management decisions for the implementation of corrective actions and opportunities for improvement as well as compare results in subsequent times.